Role of Machine Learning Techniques in Business Forecasting and Decision Making: A Review: Exploring the Impact of Machine Learning Techniques on Business Forecasting and Decision Making (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Machine learning is an application of artificial intelligence (AI) that provides systems the ability to automatically learn and improve from experience without being explicitly programmed. Machine learning focuses on the development of computer programs that can access data and use it learn for themselves. It enables analysis of massive quantities of data. Well-grounded forecasts help organizations compete in the dynamic and short-lived economy. In addition, they expand the leeway of organizations, since forecasts help them avert adverse trends in time or reinforce beneficial ones.While it generally delivers faster, more accurate results in order to identify profitable opportunities or dangerous risks, it may also require additional time and resources to train it properly. Combining machine learning with AI and cognitive technologies can make it even more effective in processing large volumes of information. The objective of this paper is to discuss work done in past by various researchers in the field of forecasting using Machine Learning.